Development and Evaluation of a Novel Instrument to Measure Severity of Intraoperative Events Using Video Data. Issue 2 (August 2020) - Jung, James J.; Jüni, Peter; Gee, Denise W.; Zak, Yulia; Cheverie, Joslin; Yoo, Jin S.; Morton, John M.; Grantcharov, Teodor
Abstract : Objective: To develop and evaluate a novel instrument to measure SEVERE processes using video data. Background: Surgical video data can serve an important role in understanding the relationship between intraoperative events and postoperative outcomes. However, a standard tool to measure severity of intraoperative events is not yet available. Methods: Items to be included in the instrument were identified through literature and video reviews. A committee of experts guided item reduction, including pilot tests and revisions, and determined weighted scores. Content validity was evaluated using a validated sensibility questionnaire. Inter-rater reliability was assessed by calculating intraclass correlation coefficient. Construct validity was evaluated on a sample of 120 patients who underwent laparoscopic Roux-en-Y gastric bypass procedure, in which comprehensive video data was obtained. Results: SEVERE index measures severity of 5 event types using ordinal scales. Each intraoperative event is given a weighted score out of 10. Inter-rater reliability was excellent [0.87 (95%-confidence interval, 0.77–0.92)]. In a sample of consecutive 120 patients undergoing gastric bypass procedures, a median of 12 events [interquartile range (IQR) 9–18] occurred per patient and bleeding was the most frequent type (median 10, IQR 7–14). The median SEVERE score per case was 11.3 (IQR 8.3–16.9). In risk-adjusted multivariable regression models, history of previous abdominal surgery ( P = 0.02) and body mass index ( P = 0.005) were associated with SEVERE scores, demonstrating construct validity evidence. Conclusion: The SEVERE index may prove to be a useful instrument in identifying patients with high risk of developing postoperative complications. Abstract : Supplemental Digital Content is available in the text